2017
DOI: 10.1080/09687599.2017.1322493
|View full text |Cite
|
Sign up to set email alerts
|

Australia’s national disability insurance scheme: looking back to shape the future

Abstract: Scheme (NDIS) provides a once-in-ageneration opportunity to transform how people with a disability are served. Similar to the enactment of the Disability Services Act 1986, which challenged the segregation and supported the integration of people with a disability into community settings, the National Disability Insurance Scheme Act 2013 is expected to fundamentally disrupt traditional service practice and improve disabled people's lives. This paper identifies some lessons from the previous reform of 1986 to gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…The NDIS defines a new era in disability service delivery across all Australian states and territories because it heralds the marketization of disability services delivery in Australia . Foster et al [2016] and Kendrick, Ward, and Chenoweth. [2017] for discussion on the challenges of equitably implementing the 'reasonable and necessary' proviso within a person-centred framework).…”
Section: The National Disability Insurance Schemementioning
confidence: 99%
See 1 more Smart Citation
“…The NDIS defines a new era in disability service delivery across all Australian states and territories because it heralds the marketization of disability services delivery in Australia . Foster et al [2016] and Kendrick, Ward, and Chenoweth. [2017] for discussion on the challenges of equitably implementing the 'reasonable and necessary' proviso within a person-centred framework).…”
Section: The National Disability Insurance Schemementioning
confidence: 99%
“…This shift in national policy and practice context demands that organisations re-invest in capacity building-for individuals and families, as well as their workforce-knowledge development, and community partnerships to sustain quality client services. Further, it has been suggested that the ambitious goals of the NDIS will only be achieved if this capacity building and investment in families as well the disability service workforce is longstanding over decades (See Kendrick et al [2017] for six lessons that can affect the success of the NDIS). Specifically, organisations will need to understand how self-direction policy can be implemented and sustained in practice.…”
Section: The National Disability Insurance Schemementioning
confidence: 99%
“…The training indicated that action and agency can be embedded into the design of a tool -enabling inspiring goals to emerge. These experiences will underlie the crucial actions for families to take as they become empowered as stressed by Kendrick, Ward and Chenoweth (2017), and start fresh conversations with professionals.…”
Section: Discussionmentioning
confidence: 99%
“…This approach provides a framework for the discussion in this paper. Discussion also explores the relationship between contemporary ideals of the National Disability Insurance Scheme (NDIS), introduced in Australia in 2013, to provide a positive change for people with a disability (Kendrick, Ward & Chenoweth 2017) and the physical and intellectual legacy of previous policy.…”
Section: Introductionmentioning
confidence: 99%